TINJAUAN YURIDIS SAHNYA PERJANJIAN TERAPEUTIK DAN PERLINDUNGAN HUKUM BAGI PASIEN - Rinaldi Syahputra; Sarina Uly; Armen Sosialisa Sihotang; Yetti (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
This research aims to determine the therapeutic validity of a treaty based on the draft Civil Law, as well as how the legal protection for patients in a therapeutic agreement. In order for the results of this study can be used as either a doctor or patient understanding in knowing the rights and obligations to be performed by physicians and patients. Based on the results of research and discussion, it can be concluded that the agreement is an agreement Ispanning therapeutic verbintenis (based on business) so it was not the outcome, but a maximum effort to cure doctor patient who becomes the object of the agreement. Basic rights which are owned by the patient is the right to information in the medical consent includes the right to know of the condition of his illness, what action will be taken by the doctor, what is the procedure, what risks may arise from the action, alternative treatment besides medical treatment that would performed.